2022
DOI: 10.3389/fphys.2021.822024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Running on Sand vs. Stable Ground on Kinetics and Muscle Activities in Individuals With Over-Pronated Feet

Abstract: Background: In terms of physiological and biomechanical characteristics, over-pronation of the feet has been associated with distinct muscle recruitment patterns and ground reaction forces during running.Objective: The aim of this study was to evaluate the effects of running on sand vs. stable ground on ground-reaction-forces (GRFs) and electromyographic (EMG) activity of lower limb muscles in individuals with over-pronated feet (OPF) compared with healthy controls.Methods: Thirty-three OPF individuals and 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…With reference to our results, we concluded that VM/VL ratios were lower in athletes with chronic knee pain in the involved limb, independently from the type of jump, surface, and origin of the knee pain in the horizontal landing phase; however, there was no crossover effect on the uninvolved side. The VM/VL EMG ratios of healthy athletes ranged between 1.24 and 1.61 in our study, which is in line with previous results by Jafarnezhadgero, reporting ratios ranging from 1.18 to 1.65 [ 60 ]. In contrast, the VM/VL ratios in the leading leg (Ø CMJ = 0.64; Ø spike = 0.65) and the providing leg (Ø CMJ = 0.52; Ø spike = 0.69) in the two excluded athletes with bilateral pain were reduced on all surfaces and jumps and even lower in the injured leading limb of unilaterally injured athletes (Ø CMJ = 0.74; Ø spike = 0.80).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With reference to our results, we concluded that VM/VL ratios were lower in athletes with chronic knee pain in the involved limb, independently from the type of jump, surface, and origin of the knee pain in the horizontal landing phase; however, there was no crossover effect on the uninvolved side. The VM/VL EMG ratios of healthy athletes ranged between 1.24 and 1.61 in our study, which is in line with previous results by Jafarnezhadgero, reporting ratios ranging from 1.18 to 1.65 [ 60 ]. In contrast, the VM/VL ratios in the leading leg (Ø CMJ = 0.64; Ø spike = 0.65) and the providing leg (Ø CMJ = 0.52; Ø spike = 0.69) in the two excluded athletes with bilateral pain were reduced on all surfaces and jumps and even lower in the injured leading limb of unilaterally injured athletes (Ø CMJ = 0.74; Ø spike = 0.80).…”
Section: Discussionsupporting
confidence: 93%
“…Jafarnezhadgero investigated neuromuscular control in healthy individuals with overpronated feet and normal feet. The VM/VL ratio increased on sand for the overpronated group (hard surface = 1.21 vs. sand = 1.65) and stayed the same for the clinically unremarkable foot group (hard surface = 1.18 vs. sand = 1.19) [ 60 ]. The results of the bilaterally injured athletes support our assumptions because the VM/VL ratio increased neither in the injured leading leg nor in the injured providing leg, with task complexity or in the sand conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high compliance of sand, the surface also acts as a damper and reduces take-off velocity ( 43 ). The combination of these biomechanical interactions with sand, result in it being a slower surface compared to harder surfaces ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study reported that a six weeks exercise program (simulated barefoot running) with three sessions per week resulted in significant decreases in loading rates and impact forces in healthy adult female runners [ 40 ]. In another study, we evaluated the acute effects of running on sand vs. stable ground and not the long-term (chronic) training effects of running on sand as performed in this study [ 42 ].…”
Section: Discussionmentioning
confidence: 99%